Physical, cognitive, social and mental health in near-centenarians and centenarians living in New York City: findings from the Fordham Centenarian Study. Issue 1 (December 2016) - Jopp, Daniela; Park, Min-Kyung; Lehrfeld, Jonathan; Paggi, Michelle
Abstract Background Despite their strong increase, the population of the very old, including near-centenarians and centenarians, represent an unstudied and underserved population. Available studies mostly concentrate on predictors of exceptional longevity, but rarely extend their focus to other areas of functioning. Also, little is known about what contributes to experiencing a quality life in very old age. The present population-based study aims at providing a comprehensive picture of key domain of functioning, including physical, cognitive, social and mental function in very old individuals and to determine predictors of mental health indicators. Methods A total of 119 individuals aged 95 to 107 living in private dwellings and residential care facilities were recruited based on the New York City Voters Registry. Participants answered questions regarding their health and activities of daily living. Their cognitive functioning was determined using the Mini-Mental State Examination and the Global Deterioration Scale. Social resources were measured with number of children and the Lubben Scale. Mental health was assessed with the Geriatric Depression Scale and the Satisfaction with Life Scale. Results An unexpectedly large proportion of the sample lived in the community. On average, cognitive functioning was high. Although five diseases were reported on average, participants reported good health. Functional status was reduced. Most participants had at least one person for communication/social support. On average, depression was below cut-off, and most participants reported high life satisfaction. Regression analyses indicated that individual differences in depression were associated with subjective health, IADL and relatives support. For life satisfaction, subjective health, ADL and number of children were most important. Demographic characteristics, number of illnesses or cognitive status were not significant. Conclusions Despite reduced levels of physical functioning and social resources, very old participants were in good mental health suggesting high resilience and ability to adapt to age-associated challenges. That a large proportion of them lived in the community further highlights their desire for leading an autonomous life, which may have been facilitated by New York service culture. More research is necessary to provide guidance for the development of well-suited services for this very old population.